O ciągu Ulama, równaniu Pella i rotacjach rynku finansowego - Florek, Jan; Juzwiszyn, Jacek; Misztal, Andrzej; Sacała, Jerzy (On Ulam sequence, Pell’s equation and rotations of the financial market, 2009)
We present a history of finance modeling and propose Ulam sequence as a tool in finance modeling
Didactics of Mathematics, 2009, Nr 5-6 (9-10), s. 5-18
Keywords: Black-Scholes model; option price; Ulam sequence; periodic continued fraction; Pell equation